Motivation in high school health instruction - Bejar, Edita Mendoza 1941- (s.n.], 1970)
The aim of the study is to determine the motivation for High School Health Instruction. Specifically, it tries to determine the significance of motivation in health instruction in the high school, the motivational principles and practices relevant to health instruction, and the motivational procedures that can be utilized in the present curricular health offerings in the high school to ensure effective and functional health instruction.